Smart Textiles for Personalized Sports and Healthcare - Ziao Xu; Chentian Zhang; Faqiang Wang; Jianyong Yu; Gang Yang; Roman A. Surmenev; Zhaoling Li; Bin Ding (Nano-Micro Letters)
Highlights This review provides comprehensive structural design strategies for the manufacturing of smart textiles, covering fibers, yarns, and fabrics and offers professional guidance for product development in this field. The fundamental performance criteria for sports-oriented smart textiles have been provided, highlighting the key attributes required for their optimal functionality in athletic applications. This review systematically introduces the diverse roles of smart textiles in specific sports scenarios and the stringent requirements they must meet to perform effectively in these environments.